A Review of Africanisation, Decolonisation and Transformation Processes to Re-Imagine and Redress Colonial-Apartheid Legacies in the South African Higher Education System - Bango, Yanda (University of Bayreuth African Studies Working Papers, 2025)
Africanisation, decolonisation and transformation are different conceptual ideas and principles that have emerged at different moments of South Africa’s (SA) history as a way of engaging with colonial-apartheid oppression and its legacies. These three discourses tend to be engaged in isolation from each other and continue to be polarised by many. This non-combined approach, however, has limitations, as it risks limiting our (re)imagination of the future of South African higher education (SAHE) from multiple perspectives. Since the dawn of South Africa’s democracy, transformation has been a favoured discourse and conceptual framework. However, the 2015 Fallist protests revealed that the transformation approach, when applied alone, cannot adequately redress South Africa’s colonial-apartheid legacies in higher education; there is a need to include and be inherently guided by the anti-oppression ideologies that informed resistance against colonialism and apartheid because they articulate(d) a particular vision for what a liberated South Africa should look like. Inspired by Es’kia Mphahlele – who believed that after independence new ideas will demand expression and create organs of public opinion, and a hybridity of ideas will rid formerly oppressed societies of their oppressive practices – this article explores and analyses the discourses of transformation, decolonisation and Africanisation relative to the South African higher education system. Having considered South Africa’s history of colonialism and apartheid, and how it has impacted the present day higher education system, I ultimately propose a hybrid-pluriversal approach that combines insights from all three frameworks. Potentially, this approach can positively impact the ongoing process of redressing colonial-apartheid legacies in the South African education system.
Keywords: Africanisation; Decolonisation; transformation; education system; Colonialism; Apartheid; pluriversality; South Africa; Mphahlele; anti-oppression ideology; Fallist protests